L’industrie de l’amiante - Dauphin, Roma (Études internationales, 1979)
This study is comprised of two parts. The first is essentially descriptive and seeks to define with greater precision the nature of the Western world's asbestos fiber needs, account being made currently-known technology and the existence of substitutes. Asbestos ore reserves are then examined with a view to evaluating the constraints conditioning current asbestos fiber production. With the exception of that carried out in the U.S.S.R., this production is highly concentrated in Quebec whose surplus output is exported to every continent at prices that have experienced a staggering increase since 1973 even though international trade in asbestos fibers is conducted via multinational firms.The second part of the study contains a cost-benefit analysis of Quebec's new policy as well as a brief consideration of the political forces that have induced the Government of Quebec to adopt it.